The Relationship between online game addiction and adolescent sleep disorders - Muhammad Sahlan Zamaa; Kamariana K; Andi Nur Annisa (An Idea Health Journal, 2022)
Online game addiction as a mental disorder for the first time in ICD-11. Online game addiction has several characteristics, including a pattern of continuous play behavior which is characterized by impaired control over the game, so that games are prioritized over other necessities of life. This study aims to determine the relationship between online game addiction and sleep pattern disorders in adolescents in BTP Blok AF RW 05/07 Kel. Consider Kec. Biringkanaya Makassar City. The type of research used in this study is an analytic survey with a cross sectional approach by analyzing the causal relationship between the two variables studied. The population in this study was 689, while the sample obtained was 228 people. The results obtained were as many as 222 teenagers who experienced Online Game Addiction while as many as 224 teenagers who experienced sleep pattern disorders. The results of the analysis using the chi-square test were obtained at 0.005 < 0.05 so it can be said that there is a significant relationship between online game addiction and sleep pattern disorders. The conclusion of this study is that more people are addicted to online games with disturbed sleep patterns and there is a relationship between online game addiction and sleep pattern disorders. It is recommended that families / parents can provide supervision regarding the dangers of Online Game Addiction in adolescents from an early age.